Lactococcus lactis Endocarditis in an Immunocompromised Patient. (8th November 2022) - Mitchell, Austin; Gorn, Sarah; Cheung, Alex; Khan, Spogmai; Anneski, Cynthia
Abstract : Lactococcus lactis infections are rarely reported in the medical literature. L. lactis is a commonly used fermenting agent which may be difficult to identify with common microbiology identification processes. This factor may contribute to its lack of recognition in medical journals. We report a case of an immunosuppressed 80-year-old female with L. lactis bacteremia, subsequently, found to have aortic valve vegetation, who responded clinically to a six-week duration of ceftriaxone therapy. Afterward, a brief updated literature review is presented on L. lactis infections.